MRSA in Stealth Mode Evades Antibody Recognition. Issue 2 (February 2019) - Passalacqua, Karla D.; O'Riordan, Mary X.
Abstract : In Nature, Gerlach et al . ( Nature 2018;563:705–709) report that methicillin-resistant Staphylococcus aureus camouflages its surface by displaying a 'stealth' wall teichoic acid (WTA) isomer. WTA can act as a cloak to limit exposure of surface antigens to the immune system, but this report indicates that even the cloak can become immunologically silent.